Sexual citizenship in the Portuguese press after the Carnation Revolution - Isabel Marques Freire (Universidade Federal de Santa Catarina, 2019)
Expecting to contribute for the debate on social change of affective and sexual intimacy in Portugal in transition from dictatorship to democracy, I analysed the content of four magazines and newspapers (Mulher - Modas & Bordados, Crónica Feminina, Expresso and Diário de Lisboa), published between 1968 and 1978. What is being said in the press about gender and sexual rights during this euphoric moment lived after the Carnation Revolution? In this article I analyze a letter, a manifest and a report, of extreme relevance for the setting of topics concerned to sexual citizenship in the media's agenda shortly after the Carnation Revolution. The three discourses associate political freedom with sexual freedom, and discuss our intimate experiences as a public and citizenship issue: the sexual story of an adolescent (Gisela) sent to a women's magazine; the first Portuguese homosexual manifest published in the press two weeks after the Carnation Revolution; and a document signed by 500 prostitutes (claiming social and political rights) that is brought to a meeting of the feminist Movimento Democrático da Mulher. In the analyzed press, the right to premarital female sexuality (claimed by Gisela), the right to «homosexual free practice» and the right to «free love» marked the emergence of a sexual citizenship (or intimate citizenship) in this period. However, only the personal sexual story of Gisela leads to a long debate on the importance of the issues of intimacy for democracy, between the readers.